EFFECTIVENESS OF LIQCORIS ORGANIC PESTICIDE AS GROWTH INHIBITOR OF PLANT PATHOGENIC MICROORGANISMS - Risa Rosita; Deden Dewantara Eris; Misbakhul Bait; Zulhamsyah Imran; Sri Widayanti; Evelyn V. Bigcas; Wachju Subchan (SEAMEO BIOTROP, 2025)
Article Highlights:- First study on Liqcoris, an organic pesticide made from coconut waste.- 15% Liqcoris concentration effectively inhibits pests and plant pathogens.- Active compounds include phenol and carbamic acid.- Pest and fungal pathogens were isolated directly from diseased plants in a school garden.- Coconut waste-based pesticide offers practical, eco-friendly pest control solutions. Abstract:Sustainable control of plant diseases is essential to maintain biodiversity. Learning using prototypes is an effort to support students in understanding and learning science and technology in order to answer problems related to biodiversity loss. The research aimed to: 1) produce a prototype of Liqcoris organic pesticide (BLM 06) from coconut shell and shell waste, 2) measure the ability of the Liqcoris organic pesticide in inhibiting the growth of plant pathogenic microorganisms, and 3) study the content of Liqcoris organic pesticide. The data obtained were statistically analyzed using the SAS Version 9.0 program. The analysis carried out was the analysis of variance (ANOVA). Duncan's advanced test was used at the 5% level to determine the differences among the treatments, i.e., 00 = control or without PDA + pesticide; 10 = PDA + pesticide concentration 10%; 15 = PDA + pesticide concentration 15%, 20 = PDA + pesticide concentration 20%, and 25 = PDA + pesticide concentration 25%. Based on in vitro test, the study showed that Liqcoris concentration of 15% proved effective in killing phytopathogen fungi (P < 0.05), including Fusarium equiseti, Fusarium graminearum, Nigrospora sphaerica and Colletotrichum gloeosporioides. Treatments with various concentrations of 15%, 20%, and 25% effectively produced inhibitory values ​​in the diameter of pathogenic fungal colonies, respectively 0.118 cm, 0.000 cm, and 0.000 cm that were significantly different from concentrations of 10% (2.7140 cm) and control 0% (5.2180 cm). Considering the economic value of production, the best concentration of organic pesticides chosen was 15%. On the other hand, in vivo test results indicated that in controlling mosaic viruses on diseased curly chili variety TM 999, without Liqcoris treatment (control), the intensity of disease attack increased by 20.22% after 6 weeks after treatment (wat). Meanwhile, after applying Liqcoris organic pesticide with a concentration of 15%, the percentage of mosaic virus attacks decreased to 2.72% after 6 wat (P < 0.05). This study showed that the content of 15% Liqcoris organic pesticide was dominated by active compound phenol (35.16%) and carbamic acid, phenyl ester (23.61%).